The RNA-binding protein Puf5 and the HMGB protein Ixr1 regulate cell cycle-specific expression of CLB1 and CLB2 in Saccharomyces cerevisiae. - Megumi Sato; Varsha Rana; Yasuyuki Suda; Tomoaki Mizuno; Kenji Irie (PLoS ONE)
Clb1 and Clb2 are functionally redundant B-type cyclins, and the clb1Δ clb2Δ double mutant is lethal. In normal mitotic growth, Clb2 plays the central role in the G2-M progression. We previously demonstrated that the RNA-binding protein Puf5 positively regulates CLB1 expression by downregulating expression of the repressor Ixr1. The decreased expression of CLB1 by the puf5Δ mutation caused a severe growth defect of the puf5Δ clb2Δ double mutant. On the contrary, CLB2 expression was unchanged between wild-type strain and puf5Δ mutant in unsynchronized cultures, and the puf5Δ clb1Δ double mutant did not show growth retardation. Therefore, we assumed that CLB1 is the main target of Puf5 in the previous study. However, considering that CLB1 and CLB2 reportedly undergo a similar expression pattern during the cell cycle, we re-examined CLB2 expression in the puf5Δ mutant in cell cycle-synchronized cultures and found that CLB2 expression was decreased in the puf5Δ mutant strain. Deletion of IXR1 restored the decreased expression of CLB2 caused by the puf5Δ mutation. Moreover, we clarified that the decreased expression of CLB2 caused by the puf5Δ mutation resulted in the growth defect in the S-phase cyclin deficient condition: the puf5Δ clb1Δ clb5Δ clb6Δ quadruple mutant grew worse than clb1Δ clb5Δ clb6Δ triple mutant, and the slow growth of the puf5Δ clb1Δ clb5Δ clb6Δ quadruple mutant was suppressed by CLB2 overexpression. Moreover, the ixr1Δ mutation is known to be synthetically lethal with deletion of the DUN1 gene encoding the checkpoint kinase. We found that the clb2Δ mutation restored the lethality of ixr1Δ dun1Δ double mutant. Our results suggest that Puf5 and Ixr1 regulate the cell cycle-specific expression of both CLB1 and CLB2, that Clb5 and Clb6 have overlapping roles with Clb1 and Clb2, and that the regulation of CLB1 and CLB2 expression by Puf5 and Ixr1 is related to the function of Dun1 kinase.